(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper presents the results of several slips and chemical reactions on MHD unstable heat and mass transmission flow over permeable stretching layer that moves with non-uniform velocity, suction/injection, Soret effect, thermal radiation, taking into account the time-dependent magnetic field applied. The controlling partial differential equations are translated into a system of coupled nonlinear differential equations with the assistance of appropriate transformations of similarity. With the help of bvp4c with the shooting process, the corresponding equations are numerically solved. Different parameter effects on velocity, temperature, and concentration profiles are addressed with the help of graphs. The rates of skin coefficient of friction, heat and mass transfer are often concerned with the aid of tables. The study already conducted is contrasted and considered to be in substantial alignment with this analysis.